Climate change, environmental regulations, and firms' efforts to reduce pollutant emissions - Xiao, Zehua; Cai, Cheng; Wang, Lumeng; Ma, Yigeng (Frontiers in Ecology and Evolution, 2023)
Environmental regulation is an important tool for achieving environmental protection. This study investigated how climate change affects firms' actions to reduce pollutant emissions through environmental regulations. We conducted a pooled OLS regression analysis using data from Chinese industrial firms that were above the designated size from 2006 to 2013. The results showed that firms reduce SO2 emissions in response to climate change, particularly when environmental regulations are more stringent. However, firms prefer to reduce productivity and implement “end-of-pipe” interventions than engage in more green innovation. Our findings highlight how firms deal with climate change under the pressure of environmental regulations and whether ecological considerations align or conflict with economic goals.